A survey on thoughts and behaviours of eating disorders among undergraduate students in a private university in Kajang - Lam, June Yun Kei (2022)
Eating disorders are complicated mental conditions and have shown to have the highest mortality rate among all psychiatric diseases. About 1 in every 5 university students are at risk of getting eating disorders. People with eating disorders can have high levels of thoughts and behavioural disturbances. Eating disorders thoughts and behaviours are significantly correlated. However, limited studies were found to be relating thoughts of ED with behaviours of ED in Malaysia. To assess the thoughts and behaviours of undergraduate students on eating disorders in a private university in Kajang, Malaysia. A cross-sectional survey study will be carried out among 234 undergraduate students in a private university in Kajang. Convenience sampling will be used to recruit participants that fit the inclusion and exclusion criteria. The questionnaire will be divided into three sections to assess sociodemographic data, thoughts of eating disorders, and behaviours of eating disorders. Data collected will be analysed using SPSS version 22. : This research focuses on thoughts and behaviours of eating disorders among undergraduate students in a private university. The findings can be used to formulate interventions to increase awareness towards eating disorders.